Crosslinking and scission in polymers - NATO Advanced Study Institute on "Advanced Methods of Determination of Crosslinking and Scission in Polymers and their Effects on Mechanical Properties" (1988 : Kemer, Kemer Bucagi, Antalya Ili, Turkey); Guven, O. (Olgun); North Atlantic Treaty Organization. Scientific Affairs Division (Dordrecht : Kluwer Academic Publishers, 1990)
09